2000
DOI: 10.1046/j.1365-2958.2000.01745.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the flagellar regulatory protein FlrC is necessary for Vibrio cholerae motility and enhanced colonization

Abstract: SummaryThe human pathogen Vibrio cholerae specifically expresses virulence factors within the host, including cholera toxin (CT) and the toxin co-regulated pilus (TCP), which allow it to colonize the intestine and cause disease. V. cholerae is a highly motile organism by virtue of a polar flagellum, and motility has been inferred to be an important aspect of virulence, yet the exact role of motility in pathogenesis has remained undefined. The two-component regulatory system FlrB/FlrC is required for polar flag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
121
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(124 citation statements)
references
References 44 publications
3
121
0
Order By: Relevance
“…The homologous gene clusters are shown in Table 4. Much is known about the role of the gene products in flagellar regulation in V. cholerae and P. aeruginosa (4,35,89,153). Based on these studies, the following model has been proposed.…”
Section: Early Gene Expression: Master Regulatory Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The homologous gene clusters are shown in Table 4. Much is known about the role of the gene products in flagellar regulation in V. cholerae and P. aeruginosa (4,35,89,153). Based on these studies, the following model has been proposed.…”
Section: Early Gene Expression: Master Regulatory Proteinsmentioning
confidence: 99%
“…V. cholerae FlrB (the FlaL homolog) is an autokinase that can transfer phosphate to FlrC (the FlaM homolog), specifically to the aspartate that is equivalent to Asp57 of CheY. FlrC must be phosphorylated to activate flagellar gene transcription (35).…”
Section: Early Gene Expression: Master Regulatory Proteinsmentioning
confidence: 99%
“…Phosphorylation of the conserved aspartate residue (D54) in the response regulatory N-terminal domain by the histidine kinase FlrB is required for FlrC-dependent transcriptional activation, as well as enhanced intestinal colonization (5,21). FlrC shares homology over its entire length with the well-characterized 54 -dependent response regulator NtrC, and thus its mechanism of transcription activation can be inferred from studies on NtrC (29).…”
mentioning
confidence: 99%
“…studied (26), as well as in Pseudomonas aeruginosa (7) and Campylobacter jejuni (14,17), suggesting that similar mechanisms underlie the regulation of class III genes in polar flagellates. Our previous results showed that strains containing FlrC locked into an inactive (D54A) or constitutively active (M114I) state demonstrated more severe defects in intestinal colonization than strains lacking FlrC entirely (5). We reasoned that this observation could be due to a repressive effect of FlrC binding upon some gene(s) necessary for V. cholerae virulence, and undertook the characterization of FlrC DNA binding.…”
mentioning
confidence: 99%
“…The V. cholerae genome encodes multiple flagellin genes (fllaABCDE), but only flagellin mutants lacking FlaA are nonflagellated Klose & Mekalanos, 1998a). The expression of motility requires a hierarchical regulatory cascade involving the alternative RNA polymerase (RNAP) subunits,  54 and  28 and the  54 -dependent transcriptional activators, FlrA and FlrC (Correa et al, 2004;Correa et al, 2000;Prouty et al, 2001;Syed et al, 2009). …”
Section: Fig 3 Regulation Of Ct and Tcp Expressionmentioning
confidence: 99%